Concurrent sickle cell anemia and alpha-thalassemia. Effect on pathological properties of sickle erythrocytes. - Embury, S H (1984)
The concurrence of sickle cell anemia and alpha-thalassemia results in less severe hemolytic anemia apparently as a result of reduced intraerythrocytic concentration of hemoglobin S and its retarded polymerization. We have evaluated the effect of alpha-globin gene number on several interrelated properties of sickle erythrocytes (RBC) that are expected to correlate with the hemolytic and rheologic consequences of sickle cell disease. The irreversibly sickled cell number, proportion of very dense sickle RBC, and diminished deformability of sickle RBC each varied directly with alpha-globin gene number. Sickle RBC density was a direct function of the mean corpuscular hemoglobin concentration (MCHC). Even in nonsickle RBC, alpha-globin gene number varied directly with RBC density. Despite differences in alpha-globin gene number, sickle RBC of the same density had the same degree of deformability and dehydration. These data indicate that the fundamental effect of alpha-thalassemia is to inhibit the generation of sickle RBC having high density and MCHC, and that the other beneficial effects of sickle RBC are secondary to this process. The less consistent effect on overall clinical severity reported for subjects with this concurrence may reflect an undefined detrimental effect of alpha-thalassemia, possibly on the whole blood viscosity or on sickle RBC membrane-mediated adherence phenomena.